Effects of inhaled histamine, methacholine and capsaicin on sputum levels of alpha 2-macroglobulin. Issue 11 (November 1997) - Halldorsdottir, H; Greiff, L; Wollmer, P; Andersson, M; Svensson, C; Alkner, U; Persson, C G
Abstract : BACKGROUND: Plasma exudation-derived proteins and peptides contribute significantly to inflammation in the airway mucosa in vivo. In the guinea pig trachea both histamine and the neurogenic stimulant capsaicin produce acute mucosal tissue distribution and luminal entry of bulk plasma, whereas cholinergic agonists fail to produce this effect. Of these agents, only histamine induces mucosal exudation of plasma in human nasal airways. The exudative effect of the above agents on human bronchi remains unknown. METHODS: The bronchial exudative responses to inhalation of histamine, methacholine, and capsaicin were examined in two groups of healthy volunteers. Sputum was induced on three occasions in each study group by inhalation of hypertonic saline (4.5%) given as an aerosol for 40 minutes using an ultrasonic nebuliser. The second and third occasions were preceded by histamine and capsaicin challenges in the first study group, and by histamine and methacholine challenges in the second study group. Histamine and methacholine were given in cumulative doses (total doses 3160 micrograms, respectively) or until a 20% reduction in forced expiratory volume in one second (FEV1) was achieved. Cumulative doses of capsaicin were inhaled until coughing prevented the subjects from drawing a full breath. Sputum levels of alpha 2-macroglobulin (729 kDa) were measured as an index of mucosal exudation of bulk plasma. RESULTS: Histamine increased mean (SE) sputum levels of alpha 2-macroglobulin from 2.72 (1.01) micrograms/ml (95% confidence interval (CI) 0.49 to 4.94) to 18.38 (8.03) micrograms/ml (95% CI 0.49 to 36.27) in the first group, and from 1.66 (0.84) micrograms/ml (95% CI -0.18 to 3.49) to 9.43 (3.63) micrograms/ml (95% CI 1.59 to 17.27) in the second group. In contrast, capsaicin evoked no exudation (sputum levels of alpha 2-macroglobulin 1.21 (0.28) micrograms/ml (95% CI 0.59 to 1.83)) and methacholine produced a minor increase in sputum levels of alpha 2-macroglobulin (2.90 (0.92) micrograms/ml (95% CI 0.90 to 4.89)). CONCLUSIONS: These results indicate that histamine is a useful agent for studying bronchial exudative responsiveness in man and that exudative effects are only of marginal importance in the cough and bronchoconstriction produced by capsaicin and methacholine.